Herramientas para el desarrollo de infraestructura Etnoeducativa con estándares de diseño adaptado al contexto cultural y alineado con las prácticas ancestrales de y para el pueblo indígena Wayúu, en La Alta Guajira. (2023)
APÜ'ÜYA ASHATAA (Keeper of Knowledge), is the result of a research methodology that delves into the search for an ideal architectural design for an ethno-educational infrastructure with quality to maintain and preserve the cultural identity and ancestral knowledge of the Wayúu indigenous people in La Alta Guajira. The content of this work covers the study of a political, economic, sociocultural and territorial context of Alta Guajira, which in this case is reflected from a first stage of research and diagnosis in relation to theoretical references and documents; a second stage of contextualization with a focus on a participatory workshop with the community of the Ethnoeducational Center No. 11 (Jarijiñamana Meridai) of La Alta Guajira, as well as an analysis - normative result and finally design tools are created for the development of Ethnoeducational infrastructure with Design standards adapted to the cultural context and aligned with the ancestral practices of and for the Wayúu indigenous people in La Alta Guajira.